Rozważania na temat Sejmu Wielkiego (w 220. rocznicę inauguracji obrad) - Szczygielski, Wojciech (Przegląd Nauk Historycznych, 2008)
The Great Seym, also called the Four Years' Seym (6th October 1788-29th May 1792), was dominated by the independence oriented deputies, who turned into a gentry parliamentary formation as an independent political subject. Having no real leadership of its own, this political formation was bound to be influenced by political and reformatory initiatives first of the Puławy party, headed by Ignacy Potocki, who represented a radically republican character of reforms (at the beginning of the Seym) and then the initiatives of the King (in the second stage of the debates). The great Seym formed a Confederation (on the initiative of the gentry) and took decisions on all questions by a simple majority vote. At the beginning of the Seym debates, the independence oriented deputies cooperating with the Puławy party, who were the advocates of the pro-Prussian orientation, liberated Poland from Russian dependence (the abolition of the War Department on the 3rd November 1788 and of the Permanent Council on the 19th January 1789). At the turn of 1788 and 1789 the Great Seym became the permanent governing Seym (permanently in session and combining legislative and executive powers) as the gentry wanted and in the future it was supposed to be the ready Seym as the Puławy party wanted. The enlightened middle gentry became the real sovereign of the Commonwealth. In the first stage of the debates (1788-1790) the Puławy party politically overpowering the king, who defended the Permanent Council (dependent on Russia), took over the reformatory initiative and combined several proposals concerning the State's political system with the idea of independence. Thanks to this they facilitated the social acceptance of the reforms in the future constitution. The gentry parliamentary formation cooperating with the Puławy party and emphasizing their own identity formed the framework of a new enlightened model of a gentry dominated state. Ater the King had joined the Polish-Prussian alliance in March 1790, the gentry following the traditional slogan: "The King with the People, the People with the King", supported Stanisław August. In the parliamentary elections in November 1790 the King's followers gained more than 60% seats in the Parliament and it was the newly elected deputies who helped the King to realize his constitutional ideas (since the election the Seym consisted of the old deputies and the newly elected ones). Consequently, a number of Ignacy Potocki's radically republican reforms lost their popularity. The main author of the Constitution Third of May was the King but in fact the Constitution and all the Third of May reforms were a result of a mutual compromise of three political subjects: the King, the Puławy party and the gentry parliamentary formation. The Constitution Third of May considerably reformed the State's political system forming a constitutional-parliamentary monarchy; the succession to the throne was introduced and the sovereignty of the Seym was strongly emphasized. The Constitution Third of May also introduced an advanced municipal reform and initiated the reform concerning the problem of peasants. The Seym debates were interrupted by the military intervention of Russia.